When and where does it pay to be green? A look into socially responsible investing and the cost of equity capital - Yanbing Wang; Michael S. Delgado; Jin Xu (International Journal of Corporate Social Responsibility (JCSR), 2023)
We investigate the circumstances under which socially responsible investing (SRI) enhances firm long-term financial performance, and therefore provides incentives for firms to self-regulate their environmental performance. Aggregating portfolios across SRI mutual funds, we estimate the effect of SRI investment with environmental screening criteria on firm cost of equity capital. We find that accounting for interactions between firm and non-shareholder stakeholders, and potential agency costs associated with certain environmental activities of the firm, SRI can facilitate the alignment of firms' environmental and financial goals. We also find that an industry group's environmental performance and diversity influence the extent to which a firm in that group can benefit from SRI investment.
Keywords: 650; Corporate environmental performance; Corporate social responsibility; Environmental self-regulation; Environmental; social; ~corporate governance; Socially responsible investing